2021
DOI: 10.1021/acsami.1c09307
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Integrated Scaffolds for Biologically Functional DNA Origami Structures

Abstract: The manufacture of DNA origami nanostructures with highly ordered functional motifs is of great significance for biomedical applications. Here, we present a robust strategy to produce customized scaffolds with integrated aptamer sequences, which enables direct construction of functional DNA origami structures. As we demonstrated, aptamers of various numbers and types were efficiently and stably integrated in userdefined positions of the scaffolds. Specifically, two different thrombin aptamer sequences were sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Furthermore, a semi-automatic software allows the user to examine the design status at several stages, modify details from default settings, and seamlessly move forward and backward through the design steps, all of which is facilitated by rapid feedback in GUIs to visualize results of design choices. Furthermore, the new design paradigm introduced here can fully leverage the growing library of scaffold sources (40)(41)(42)(43), removing restrictions in spatial dimensions and allowing users to realize even more diverse structures. For example, we used the multi-scaffold feature of MagicDNA to achieve large structures, such as the "FNANO" script (Fig.…”
Section: Versatile Design Framework and Hierarchical Assemblymentioning
confidence: 99%
“…Furthermore, a semi-automatic software allows the user to examine the design status at several stages, modify details from default settings, and seamlessly move forward and backward through the design steps, all of which is facilitated by rapid feedback in GUIs to visualize results of design choices. Furthermore, the new design paradigm introduced here can fully leverage the growing library of scaffold sources (40)(41)(42)(43), removing restrictions in spatial dimensions and allowing users to realize even more diverse structures. For example, we used the multi-scaffold feature of MagicDNA to achieve large structures, such as the "FNANO" script (Fig.…”
Section: Versatile Design Framework and Hierarchical Assemblymentioning
confidence: 99%
“…[87][88][89] Through varying covalent bonding methods, shape and size, DNA-protein reactions and nucleic acid pairing, there is an interaction between DNA nanostructures and various functional molecules which help established its foundation in cellular drug delivery. 90 For example, Chen et al 91 successfully constructed some DNA scaffolds that binding to PDGF inducers and investigating their suppressor effect on MDA-MB-231 in the breast cancer cells. The result showed DNA origami product designated a strong inhibitory effect, and further inspired people with a new thought of building more stable and functional DNA origami structures.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…34−36 Recently, a study by Chen et al used bacteriophage genome modifications to introduce multiple aptamers at specific locations on folded structures. 37 Although this method can generate a large amount of scaffold (greater than milligram quantity) and is highly efficient for the introduction of aptamers via sequence modification, bacteriophage production of ssDNA does not allow chemical functionalization and still requires the use of modified oligonucleotides to further functionalize the folded DNA-NPs. 37−39 As an alternative, polymerase chain reaction (PCR)-based strategies, particularly the asymmetric PCR (aPCR) method, offer a higher flexibility in sequence design and sequence length and can be used for direct incorporation of functional groups into the scaffold during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, only a few studies have demonstrated the production of functional DNA origami scaffolds, but these approaches are mainly focused on tuning the size and sequence of scaffolds to overcome the length limitation inherent to commercially available versions of M13mp18. − Recently, a study by Chen et al. used bacteriophage genome modifications to introduce multiple aptamers at specific locations on folded structures . Although this method can generate a large amount of scaffold (greater than milligram quantity) and is highly efficient for the introduction of aptamers via sequence modification, bacteriophage production of ssDNA does not allow chemical functionalization and still requires the use of modified oligonucleotides to further functionalize the folded DNA-NPs. − …”
Section: Introductionmentioning
confidence: 99%